PERUBAHAN BUNYI VOKAL PADA KATA SERAPAN BAHASA ARAB DALAM BAHASA INGGRIS - Tatu Siti Rohbiah; Tajudin Nur; Wahya Wahya; Gugun Gunardi (English Department FBS UNP, 2019)
This research aims to analyze and formulate rules of change that occur in Arabic borrowings in English phonologically. Thus research can describes vocal sound changes in Arabic borrowings in English. This research is to answer the question such as how are the process of monophthong and diphthong vowel changes in Arabic borrowings in English. This research is a qualitative type which is analyzed and written descriptively to answer how the process of changing phonologically with a method consisting of three stages, namely: (1) data codification method, (2) data analysis method, and (3) method of presenting the results of data analysis and the data source used by researcher froms Oxford Advanced Learners Dictionary and Al-Maurid: A Modern Arabic-English Dictionary, and also from magazines such as Time, Bloomberg Business Week, and News Scientist. The result findings are 103 words in Arabic borrowings in English that were analyzed, it was found phonological changes on monophthong and diphthong vowel sounds caused by the unavailability of the type of Arabic sound in English and the influence of sound falling before and after it.